2016
DOI: 10.1097/spv.0000000000000238
|View full text |Cite
|
Sign up to set email alerts
|

To Pack or Not to Pack? A Randomized Trial of Vaginal Packing After Vaginal Reconstructive Surgery

Abstract: Although there was no difference based on VAS, women receiving vaginal packing had lower nursing documented pain and used less ketorolac than packed women. Vaginal packing may provide benefit and can remain part of the surgical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…). After duplicates had been excluded, we identified 31 trials including 27 primary interventional RCTs and four follow‐up studies . Seventeen studies were included in the posterior repair group (14 first studies and 3 follow‐up studies) and 14 in the multicompartmental group (13 first studies and one follow‐up study).…”
Section: Resultssupporting
confidence: 77%
“…). After duplicates had been excluded, we identified 31 trials including 27 primary interventional RCTs and four follow‐up studies . Seventeen studies were included in the posterior repair group (14 first studies and 3 follow‐up studies) and 14 in the multicompartmental group (13 first studies and one follow‐up study).…”
Section: Resultssupporting
confidence: 77%
“…Data regarding the utility of vaginal packing are mixed [185], and in circumstances of suspected bleeding it may be beneficial, but in general it should be avoided because it causes discomfort, delays urinary catheter discontinuation, and limits ambulation [173]. Options for discontinuation of urinary catheters and/or vaginal packing among patients otherwise meeting discharge milestones include return to an outpatient nursing clinic or a homecare nursing visit depending on insurance.…”
Section: The Postoperative Care Phasementioning
confidence: 99%
“…We obtained data from two trials, which included women undergoing similar surgical procedures and receiving similar postoperative care, exclusively from conference abstracts (13,14). The other two trials assessed pain as the main outcome (15,16), and one of these also assessed postoperative blood loss (16). The risk of bias from the trials varied, and of note, the trials reported as conference abstracts provided little detail on their study design but were described as randomized (13,14).…”
Section: Descriptive Analysismentioning
confidence: 99%
“…The risk of bias from the trials varied, and of note, the trials reported as conference abstracts provided little detail on their study design but were described as randomized (13,14). Risk of selection bias was low in the other two trials, which also implemented strategies to blind the participants and the staff responsible for the outcome evaluation (15,16).…”
Section: Descriptive Analysismentioning
confidence: 99%
See 1 more Smart Citation